Rancang Bangun Alat Pencampur Pakan Ikan Dengan Mekanisme Sistem Gerak Rotary Menggunakan Metode VDI 2221 - salem, arianto; mangesa, daud pulo; Maliwemu, Erich (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
Along with the development of science and technology, this is what supports making a fish feed mixing machine. The main goal in creating this technological innovation is so that the results obtained are more effective, efficient and of high quality. The manufacture of this tool has gone through several processes of theoretical calculation of the forces that occur when the machine is working, the selection of component materials, and the process of working on then assembling the components of the machine, testing the performance of the machine according to the design with animal feed materials. In this design, the mechanical system of the fish feed mixing machine the source of the rotation is a gear motor that moves the belt and pulley which is directly connected to the reduser which then moves the Mixing shaft with chains and sprockets as an introduction. Keywords : Fish Meal, Bone Meal, Shrimp. Mixing Machine,VDI Method 2221.